The Effect of Environmental CSR on Positive Emotions, Attitudes & Corporate Reputation - Dimas Adhi Kelana; Kurniawati Kurniawati (International Journal Labs, 2024)
This study aims to analyze the influence of environmental Corporate Social Responsibility on positive emotions, attitudes, and company reputation. This research uses quantitative approach method. The results of this study also confirm that the role of positive emotions has striking significance in the conceptual structure used. This suggests that within a developed frame of mind, positive emotions play an important central role. The conclusion of this study is that there is a positive correlation between environmental CSR with positive emotions and company reputation. In addition, there is also a positive correlation between the company's reputation and positive emotions and attitudes towards the company.